Dispersing anti-gel functional PVDF material for positive electrode slurry and preparation method thereof

By preparing dispersed antigel functional PVDF materials by using the reaction extrusion method in the lithium battery positive electrode slurry, the problem of slurry gelation is solved, the dispersion stability and antigel performance are significantly improved, and the applicability and production efficiency of the material are enhanced.

CN119661782AActive Publication Date: 2025-03-21ZHENGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411701153.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-21
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing lithium battery positive electrode slurry is prone to gelation during the preparation process, resulting in high viscosity, poor stability and functional failure. The existing improved methods have problems with the reduction in the proportion of active materials, stability and compatibility caused by the introduction of additives.

Method used

The dispersed antigel functional PVDF material was prepared by reaction extrusion method. By introducing the co-grafting functional part, the dispersed functional part and the antigel functional part, the double screw high-temperature shearing action was used to uniformly mix and graft reaction to form a PVDF material with excellent dispersion stability and antigel performance.

Benefits of technology

The dispersion stability and anti-gel characteristics of the lithium battery positive electrode slurry are significantly improved, the viscosity is reduced, the bonding performance and compatibility is enhanced, the gelation problem is avoided, and the material applicability and production efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661782A_ABST
    Figure CN119661782A_ABST
Patent Text Reader

Abstract

The invention relates to a PVDF (Polyvinylidene Fluoride) material with a dispersing and anti-gel function for positive electrode slurry, and the PVDF material has the following structural formula: # imgabs0 #, wherein in the structural formula, G1 is a co-grafting functional part and comprises, but not limited to, one or more of vinyl trimethoxy silane, styrene ethyl trimethoxy silane, 3-(methylacryloyloxy) propyl trimethoxy silane, vinyl tri (2-methoxyethoxy) silane, (4-vinyl phenyl methyl) trimethylsilane and the like. According to the PVDF material, under the condition that more added functional parts are not introduced, the dispersion stability of the existing lithium battery positive electrode slurry can be remarkably improved, the anti-gel property of the slurry is enhanced, and the applicability of the lithium battery positive electrode binding material in different slurry systems is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a dispersed anti-gel functional PVDF material for positive electrode slurry and a preparation method thereof. Background Art

[0002] With the popularity of new energy vehicles, the performance requirements for power batteries are getting higher and higher. Lithium-ion batteries are currently the most commonly used batteries in the electric vehicle industry. In the manufacturing process of lithium-ion batteries, the quality of the pole piece directly affects the electrochemical performance and safety stability of the battery, and the preparation of electrode slurry is the first and most important step in the production process of lithium-ion batteries. The viscosity, solid content, uniformity and stability of the slurry directly affect the subsequent slurry coating, electrode sheet rolling and electrode performance, so the dispersion of the slurry is crucial. In addition, in actual production, an abnormal slurry gel phenomenon is often found in different slurry systems. Once gelation occurs during the synthesis of the electrode, the form of the electrode changes from slurry to gel, loses fluidity, and loses its adhesive properties, which not only seriously affects the coating of the slurry, but also causes the separation of aluminum foil and electrode materials, and ultimately leads to the functional failure of the positive electrode material. Therefore, gelation should be prevented or slowed down as much as possible during the preparation of positive electrode materials. The current improvement methods mainly eliminate gel by adding one or two additives, or changing the pulping process. However, in fact, the introduction of additional additives will not only reduce the proportion of active materials in the battery, but also cause a series of problems such as stability and compatibility. Complex processes are not what the factory needs.

[0003] Polyvinylidene fluoride (PVDF) is currently a mainstream lithium battery positive electrode binder. Although it accounts for a small proportion in the slurry (generally 2-5wt%), it is an indispensable and important material in lithium-ion batteries. PVDF is a semi-crystalline functional fluorine-containing polymer composed of -CH 2 -CF 2 -Repeating units, its molecular chains are arranged closely and have strong hydrogen bonding interactions. However, PVDF is an inert compound with poor solubility, high system viscosity, poor compatibility with other substrate materials, and only relying on weak van der Waals forces to provide adhesion, which limits its application demand in today's competitive market. Without introducing more additives, further reducing the viscosity of the slurry system, improving the stability of the slurry and its applicability in different slurry systems is a problem that must be faced.

[0004] Therefore, it is necessary to modify PVDF, and the main modification methods are copolymerization, grafting, blending, etc. The copolymerization method generally involves copolymerizing PVDF with other fluorine-containing monomers, but it often requires the use of various additives, catalysts, etc. to react in a solution, so there are inevitably metal ion residues in the final product, which obviously cannot meet the increasingly demanding high-energy density battery industry. The blending method needs to consider the compatibility between the modified material and PVDF. If the compatibility is poor, the modified material will be unevenly dispersed or even agglomerated in the PVDF matrix, resulting in unsatisfactory product performance; in addition, when using the blending method, there is no chemical bond between the modified material and PVDF, and the modified material is prone to continuous loss during use, and cannot provide an excellent and stable modification effect.

[0005] Existing patent CN117603634A discloses a PVDF binder that can be applied to high alkaline ternary positive electrode or sodium battery positive electrode system. Although it can effectively solve the gel problem of slurry, the PVDF copolymer obtained by suspension polymerization not only uses a large amount of solvent, but also has harsh reaction conditions and cumbersome post-processing process, which is not conducive to industrial production. Patent CN117946338A discloses a PVDF material with high compatibility and adhesion and a preparation method. It uses a reactive extrusion method to melt-graft methacryloxypropyltriethoxysilane (MPTES) onto polyvinylidene fluoride (PVDF). Although this method can effectively enhance the coating adhesion of PVDF, its impact in the battery field is unknown.

[0006] In view of the above problems, there is an urgent need for a modification method of PVDF, a lithium battery positive electrode binder material, which is convenient for industrial production and can significantly improve the dispersion stability of the existing lithium battery positive electrode slurry without introducing more added functional parts, enhance the anti-gel properties of the slurry, and increase the applicability of the lithium battery positive electrode binder material in different slurry systems. Summary of the invention

[0007] The present invention aims to overcome the defects of the prior art and provide a PVDF material with anti-gel dispersion function for positive electrode slurry. The PVDF material can significantly improve the dispersion stability of the existing lithium battery positive electrode slurry, enhance the anti-gel properties of the slurry, and increase the applicability of the lithium battery positive electrode binder in different slurry systems without introducing more added functional parts.

[0008] The present invention also provides a method for preparing the above-mentioned dispersed anti-gel functional PVDF material for positive electrode slurry.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] A dispersed anti-gel functional PVDF material for positive electrode slurry, wherein the PVDF material has the following structural formula:

[0011] in,

[0012] In the above structural formula, G1 is a co-grafted functional part, including but not limited to one or more of vinyl trimethoxysilane, styrene ethyl trimethoxysilane, 3-(methacryloyloxy) propyl trimethoxysilane, vinyl tris (2-methoxyethoxy) silane, (4-vinylphenylmethyl) trimethylsilane, etc.;

[0013] In the above structural formula, G2 is a dispersing functional part, and its structure is as follows:

[0014]

[0015] In the distributed functional part G2, R 1 and R 2 The group can be a long-chain alkane structure with 1-8 carbon atoms, an olefin containing an unsaturated bond, or a cyclic structure, wherein at least one chain is carboxyl terminated; the number of repeating units x can be 10-40;

[0016] In the above structural formula, G3 is the anti-gel functional part, and its structure is as follows:

[0017]

[0018] In the anti-gel functional part G3, R 3 The group can be a hydrogen atom, a methyl group having 1 to 2 carbon atoms, or an acetyl group; R 4 , R 5 The group may be an alkyl group having 1 to 7 carbon atoms, an alkyl group having 1 to 4 carbon atoms and terminated with a hydroxyl group, or an aromatic group having 6 to 8 carbon atoms.

[0019] Furthermore, in the distributed functional part G2, R 1 and R 2 The monomers composed of the group include but are not limited to: one or more of maleic anhydride, maleic acid, α-linolenic acid, oleic acid, linoleic acid, arachidonic acid, etc.; the monomer composed of the repeating unit number x can be allyl polyethylene glycol, and the molecular weight is preferably 500-1800.

[0020] Furthermore, in the anti-gel functional part G3, R 3 and R 4 The substances composed of the group include but are not limited to: one or more of phenylhydrazine, acetylphenylhydrazine, 2-hydrazineethanol, ethylhydrazine, benzylhydrazine, etc.; 5The substances constituting the group include but are not limited to: one or more of acetic acid hydrazide, diacylhydrazide, 4-hydroxybenzoic acid hydrazide, 4-hydroxyphenylacetic acid hydrazide, caproic acid hydrazide, caprylic acid hydrazide, phenylhydrazide, phenylacetic acid hydrazide, phenoxyacetic acid hydrazide and the like.

[0021] The present invention provides a method for preparing the above-mentioned dispersed anti-gel functional PVDF material for positive electrode slurry, which comprises the following steps:

[0022] S1, drying PVDF powder in an oven;

[0023] S2, using a high-speed mixer to mix the PVDF powder with the initiator, the dispersing functional part, the co-grafting functional part, and the anti-gel functional part;

[0024] S3, start the twin-screw extruder to preheat, and set the parameters;

[0025] S4, injecting the uniformly mixed sample from the injection port of the twin-screw extruder, extruding through the twin-screw shear mixing reaction, and gradually transferring the material from the first section of the extruder to the sixth section for discharge;

[0026] S5. Pass the extruded product through a cooling water tank, dry it thoroughly, and then use a pelletizer to pelletize the product after water cooling.

[0027] Specifically, in step S1, the molecular weight of the PVDF powder is 200000-500000; the temperature of the oven is 80-120° C., and the drying time is 12-24 hours.

[0028] Furthermore, in step S2, the mass fractions of each reaction component are: 100 parts of PVDF; 0.1-0.3 parts of initiator; 5-10 parts of dispersion functional part; 1-5 parts of co-grafting functional part; 2-5 parts of anti-gel functional part; the initiator can be one or more combinations of benzoyl peroxide, diisopropylbenzene peroxide, dodecanoyl peroxide, di-tert-butylcumyl peroxide, tert-butyl perbenzoate, etc., preferably dodecanoyl peroxide.

[0029] Furthermore, in step S4, the twin-screw extruder is provided with six temperature control zones, namely: section I 80±2°C, section II 100±2°C, section III 150±2°C, section IV 170±2°C, section V 170±2°C, and section VI 175±2°C.

[0030] Furthermore, in step S4, the screw speed of the twin-screw extruder may be 30-50 rpm, the material feeding speed may be 50-60 rpm, and the average residence time of the material in the twin-screw extruder may be 3-5 min.

[0031] The invention provides a dispersed anti-gel functional PVDF material for positive electrode slurry prepared by the method.

[0032] The present invention also provides the use of the above-mentioned dispersed anti-gel functional PVDF material as positive electrode slurry for lithium batteries.

[0033] Taking one of the systems as an example, the grafting reaction principle is as follows:

[0034]

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The preparation method of the dispersed anti-gel functional PVDF material of the present invention is prepared by reactive extrusion. The strong shearing effect of the twin screw at high temperature can fully mix the functional parts of the material evenly, and the grafting is initiated by the initiator free radical, and the covalently grafted small molecules are inseparable from the PVDF main chain, which can effectively avoid phase separation / aggregation, provide excellent and stable modification effects, and increase its compatibility and applicability with different systems. In addition, it has high production efficiency, avoids the use of a large amount of organic solvents, and can be continuously industrialized, which greatly enriches the modification system of existing lithium battery positive electrode binding materials.

[0037] (2) In the preparation process of the modified PVDF material, the present invention introduces a water cooling system, which not only avoids the problem of uneven crystallization of the extruded product caused by the natural cooling process, but also can remove the water-soluble functional parts that do not participate in the grafting during the reaction extrusion process, thereby further increasing the proportion of the main components of the modified PVDF material; in addition, some grafted functional parts will be further hydrolyzed, thereby introducing more reaction sites, which will further enhance the comprehensive performance of the PVDF material.

[0038] (3) In the modification process of PVDF, the present invention introduces a dispersing functional part by grafting. Its long-chain structure can provide sufficient steric hindrance in the positive electrode slurry, reduce the chain entanglement of the PVDF molecular chain itself, and form a stable barrier. Therefore, the positive electrode slurry prepared by it has a lower viscosity and can remain stable for a longer time. In addition, due to the introduction of carboxyl groups, strong hydrogen bonds can be formed with the hydroxyl groups on the surface of the active material, further enhancing the bonding properties of the PVDF material, and the partially ionized carboxylate groups can also generate an electrostatic repulsion, which further enhances the dispersion stability of the slurry.

[0039] (4) In the modification process of PVDF, the present invention introduces an anti-gelling functional part through an amidation reaction, so that the adhesive material has a strong metal ion chelating ability, which can effectively alleviate the slurry gel problem.

[0040] (5) The present invention introduces a co-grafting functional part in the modification process of PVDF. Its inorganic functional group is reactive to inorganic materials, and its organic functional group is compatible and reactive to organic materials, playing a coupling role in the entire material system, further enhancing the compatibility between the various systems in the slurry; its co-grafting effect is not only conducive to the grafting of the dispersing functional part, but also its hydrolyzed silanol group can further react with the anti-gel functional part, so that the prepared adhesive material has more excellent performance.

[0041] (6) The dispersed anti-gel functional PVDF material prepared by the present invention undergoes high temperature and high pressure twin-screw shearing, causing the PVDF crystal form to transform from α to β crystal, improving the slow dissolution rate and high viscosity of the existing PVDF while enhancing the conductivity of PVDF. This method not only maintains the original comprehensive performance of PVDF, but also can significantly improve its dispersion performance, stability, anti-gel properties, etc., while increasing its applicability in different slurry systems, solving the gel problem existing in the existing high solid content lithium battery positive electrode slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 FT-IR spectra of PVDF and Examples 1-5;

[0043] Figure 2 XRD patterns of PVDF and Examples 1-5. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the technical solutions of the present invention are further described below in conjunction with embodiments. However, the present invention is not limited to the embodiments listed, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0046] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0047] In the examples, the molecular weight of the PVDF powder used is 200,000-500,000, and it is a common commercial product.

[0048] Example 1, a method for preparing a dispersed anti-gel functional PVDF material for positive electrode slurry comprises the following steps:

[0049] (1) Dry 400 g of PVDF in an oven at 80 °C for 24 h;

[0050] (2) 400 g PVDF, 0.4 g dodecyl peroxide, 20 g dispersing functional part (α-linolenic acid), 4 g co-grafting functional part (3-(methacryloyloxy)propyltrimethoxysilane), and 8 g anti-gel functional part (phenylhydrazine) were mixed thoroughly using a high-speed mixer;

[0051] (3) Start the twin-screw extruder, and set the six temperature control zones as follows: 80±2°C for zone I, 100±2°C for zone II, 150±2°C for zone III, 170±2°C for zone IV, 170±2°C for zone V, and 175±2°C for zone VI. After reaching the set temperature, start the screw, set the speed to 40 rpm, and set the feeding speed to 60 rpm.

[0052] (4) The mixed material is fed into the feed port of a twin-screw extruder. The material is gradually transferred from the first section to the sixth section. The material is extruded through high-temperature shear mixing reaction of the twin-screw extruder. The average residence time of the material in the twin-screw extruder is 3 minutes. The material is then discharged, cooled in a cooling water tank, and pelletized by a pelletizer to finally obtain a dispersed anti-gel functional PVDF material.

[0053] Example 2, a method for preparing a dispersed anti-gel functional PVDF material for positive electrode slurry comprises the following steps:

[0054] (1) Dry 400 g of PVDF in an oven at 120 °C for 12 h;

[0055] (2) 400 g PVDF, 0.8 g benzoyl peroxide, 40 g dispersing functional part (oleic acid), 8 g co-grafting functional part (vinyl trimethoxy silane), and 16 g anti-gel functional part (acetophenylhydrazine) were fully mixed using a high-speed mixer;

[0056] (3) Start the twin-screw extruder, and set the six temperature control zones as follows: 80±2°C for zone I, 100±2°C for zone II, 150±2°C for zone III, 170±2°C for zone IV, 170±2°C for zone V, and 175±2°C for zone VI. After reaching the set temperature, start the screw, set the speed to 50 rpm, and set the feeding speed to 50 rpm;

[0057] (4) The mixed material is fed into the feed port of a twin-screw extruder. The material is gradually transferred from the first section to the sixth section. The material is extruded through high-temperature shear mixing reaction of the twin-screw extruder. The average residence time of the material in the twin-screw extruder is 4 minutes. The material is then discharged, cooled in a cooling water tank, and pelletized by a pelletizer to finally obtain a dispersed anti-gel functional PVDF material.

[0058] Example 3, a method for preparing a dispersed anti-gel functional PVDF material for positive electrode slurry comprises the following steps:

[0059] (1) Dry 400 g of PVDF in an oven at 120 °C for 12 h;

[0060] (2) 400 g PVDF, 0.4 g di-tert-butyl isopropyl peroxide, 30 g dispersing functional part (linoleic acid), 8 g co-grafting functional part (styrene ethyl trimethoxy silane), and 16 g anti-gel functional part (4-hydroxybenzoyl hydrazide) were fully mixed using a high-speed mixer;

[0061] (3) Start the twin-screw extruder, and set the six temperature control zones as follows: 80±2°C for zone I, 100±2°C for zone II, 150±2°C for zone III, 170±2°C for zone IV, 170±2°C for zone V, and 175±2°C for zone VI. After reaching the set temperature, start the screw, set the speed to 50 rpm, and set the feeding speed to 50 rpm;

[0062] (4) The mixed material is fed into the feed port of a twin-screw extruder. The material is gradually transferred from the first section to the sixth section. The material is extruded through high-temperature shear mixing reaction of the twin-screw extruder. The average residence time of the material in the twin-screw extruder is 5 minutes. The material is then discharged, cooled in a cooling water tank, and pelletized by a pelletizer to finally obtain a dispersed anti-gel functional PVDF material.

[0063] Example 4, a method for preparing a dispersed anti-gel functional PVDF material for positive electrode slurry comprises the following steps:

[0064] Reference Example 1, except that the initiator is changed to tert-butyl perbenzoate, and the dispersing functional part is replaced by maleic anhydride.

[0065] Example 5, a method for preparing a dispersed anti-gel functional PVDF material for positive electrode slurry comprises the following steps:

[0066] Refer to Example 2, except that the anti-gel functional part is changed to hexanoyl hydrazide, and the co-grafting functional part is replaced with vinyl tris (2-methoxyethoxy) silane.

[0067] Comparative Example 1, a common commercially available PVDF.

[0068] Performance Test:

[0069] 1. Viscosity of the glue. Weigh 7g of the above-prepared dispersed anti-gel functional PVDF material in 93g of N-methylpyrrolidone NMP, and dissolve it in a 70°C oil bath with magnetic stirring to obtain the dispersed anti-gel functional PVDF material glue. Then take 30ml of the glue and transfer it to a 50ml centrifuge tube, place it in a 25°C constant temperature water bath, and use an RVDV-1 digital rotational viscometer to test it, using a No. 3 rotor, a rotation speed of 30rpm, and a test temperature of 25°C.

[0070] 2. Slurry preparation process.

[0071] First, the positive electrode active material lithium iron phosphate and the conductive agent are placed in a 120℃ oven for 4 hours. The organic solvent N-methylpyrrolidone, the PVDF material glue prepared above, and the conductive agent are placed in a 250ml plastic beaker in turn, and sheared using a high-speed shearing machine with a shearing speed of 1200rpm and a shearing time of 10min; finally, the positive electrode active material lithium iron phosphate is added, and the shearing is continued at a speed of 1500rpm for 20min to obtain the positive electrode slurry. Among them, the raw materials are weighed according to the mass ratio of lithium iron phosphate: conductive agent: dispersed anti-gel functional PVDF material = 96:2:2, and the PVDF material is the corresponding mass of the glue. In the positive electrode slurry, the content of the organic solvent N-methylpyrrolidone accounts for 32wt% of the slurry.

[0072] During the above slurry preparation process, the conductive agent selected for the sample in Example 1 is KS-15; the conductive agent selected for the sample in Example 2 is acetylene black; the conductive agent selected for the sample in Example 3 is carbon nanotubes; the conductive agent selected for the sample in Example 4 is SFG-15; and the conductive agent selected for the sample in Example 5 is Ketjen black.

[0073] 3. Slurry viscosity and gel test. Transfer 30 ml of slurry to a 50 ml centrifuge tube, place it in a constant temperature water bath at 25°C, and use RVDV-1 digital rotational viscometer to test it. The rotor used is No. 4 rotor, the speed is 12 rpm, and the test temperature is 25°C. Measure the viscosity at regular intervals and observe whether the slurry is gelled.

[0074] 4. Peel strength and folding resistance test. The evenly dispersed slurry is evenly coated on the substrate with aluminum foil as the positive electrode plate through a coating machine with a thickness of 200μm. The finished positive electrode plate is placed in a 105℃ oven for drying for 1h. Then the wet 200μm dried electrode plate is rolled and tested for peel strength. Roll to a compacted density of 2.4g / m 3 The pole piece is cut into a sample strip of 15mm×200mm and tested using a 180° horizontal peel strength tester at a speed of 150mm / min and a test temperature of 25°C. The coated side and the aluminum foil side of the sample strip are folded in half once respectively, and the folding resistance is calculated as one time until the sample strip cracks.

[0075] Figure 1 The FT-IR spectra of Examples 1-5 are shown in the figure. Compared with pure PVDF, the infrared spectra of each example have a -1 New characteristic absorption peaks appeared at 1730 cm -1 A new characteristic absorption peak appears near 1600cm -1 A new peak appeared near 3300cm, which was attributed to the vibration peak of the benzene ring of the anti-gel functional part. -1 The new characteristic peaks appearing around 100 nm are attributed to the -NH- peak of the anti-gel part. The above results show that all functional parts have been successfully grafted. And after further testing, based on the amount of PVDF, the grafting amount of the co-grafted functional part G1 is 0.05-1wt%; the grafting amount of the dispersing functional part G2 is 0.05-1wt%; and the grafting amount of the anti-gel functional part G3 is 0.05-1wt%. In addition, we observed that after the reaction extrusion, compared with the example, the 975cm- -1 and 762cm -1 The characteristic peak belonging to α crystal is weakened to a great extent, and the peak at 1276 cm-1 in the embodiment is replaced by -1 and 839cm -1 The enhancement of the peak is attributed to the β characteristic peak of PVDF, which indicates that after modification by this method, PVDF has completed the transformation from α crystal to β crystal. The β crystal has strong polarity and excellent ferroelectric and piezoelectric properties, which helps to improve the conductive properties of PVDF materials.

[0076] Figure 2 The XRD patterns of Examples 1 to 5 are shown in the figure. It can be seen that the characteristic diffraction peaks of the non-polar phase α crystal appear at 17.612°, 18.16°, 19.765° and 26.658° in pure PVDF, while after modification by the method of the present invention, the diffraction peaks in the examples appear at 18.50° and 20.15°, which belong to the diffraction peaks of the polar phase β crystal, and are consistent with the FT-IR spectrum obtained above.

[0077] Table 1 Solubility test results of Examples 1-5 and Comparative Example 1

[0078]

[0079] In the present invention, specifically, by comparing Examples 1-5 with Comparative Example 1, it can be seen that:

[0080] 1) Compared with the dissolution time of commercially available PVDF, the dissolution time of the dispersed anti-gel functional PVDF material of the present invention is reduced;

[0081] 2) Compared with commercially available PVDF, the viscosity of the adhesive material prepared by the present invention is greatly reduced, with a reduction range of 41%-63%, and can still remain stable after being stationary for 24 hours.

[0082] Table 2 Slurry performance test results of Examples 1-5 and Comparative Example 1

[0083]

[0084] In the present invention, specifically, by comparing Examples 1-5 with Comparative Example 1, it can be seen that:

[0085] 1) The positive electrode slurry prepared using the dispersed anti-gel functional PVDF material prepared by the present invention has a lower viscosity after standing for 1 hour, with the maximum decrease reaching 82.7%;

[0086] 2) After standing for 8 hours, compared with Comparative Example 1, the viscosity of the slurry of the embodiment of the present invention increased slightly, ranging from 16.6% to 35.4%, while the viscosity of the slurry of the comparative example increased by nearly 135%;

[0087] 3) After standing still for 24 hours, the positive electrode slurries prepared by the present invention did not show any gelation phenomenon, while the comparative example 1 had already gelled after standing still for 8 hours.

[0088] Table 3 Comparison of peel strength of Examples 1-5 and Comparative Example 1

[0089] sample Peel strength N / m Folding resistance Example 1 13.28 5 Example 2 14.56 5 Example 3 12.35 5 Example 4 10.26 4 Example 5 8.37 4 Comparative Example 1 6.32 1

[0090] In the present invention, specifically, by comparing Examples 1-5 with Comparative Example 1, it can be seen that:

[0091] 1) The peel strength of the positive electrode sheets prepared using the dispersed anti-gel functional PVDF material prepared by the present invention is improved, and the improvement degree is 32.43-130.38% compared with the comparative example, and the sheet has excellent folding resistance; thus reflecting the excellent bonding performance of the PVDF material as a binder, and further reflecting the excellent performance of the lithium battery positive electrode sheet.

[0092] In summary, the preparation method of a dispersed anti-gel functional PVDF material and a preparation method of a positive electrode slurry prepared by the present invention have the following beneficial effects:

[0093] The preparation method of the PVDF material with dispersed anti-gel function of the present invention is prepared by reactive extrusion, and the strong shearing effect of the twin screw at high temperature is utilized to introduce the dispersed functional part by grafting, and its long chain structure can provide sufficient steric hindrance in the positive electrode slurry, reduce the chain entanglement of the molecular chain of PVDF itself, and form a stable barrier, so that the positive electrode slurry prepared by it has lower viscosity and can maintain stability for a longer time. Through the water cooling system, not only the modified PVDF material has more uniform crystallization, but also the main component proportion of the modified PVDF material is increased, and the reaction sites are increased. By introducing the co-grafted functional part, not only the compatibility between the functional parts is further enhanced, but also the grafting rate of other functional parts is increased, so that more beneficial functional groups are linked. By introducing the anti-gel functional part, the bonding material has a strong metal ion chelating ability, which can effectively slow down the slurry gel problem. And because of the high temperature and high pressure twin screw shearing, the crystal function of PVDF is transformed from α to β crystal, which improves the slow dissolution rate and high system viscosity of the existing PVDF, and enhances the conductivity of PVDF. It not only maintains the original comprehensive performance of PVDF, but also can significantly improve its dispersion performance, stability, anti-gelling properties, etc.

[0094] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A dispersed anti-gel functional PVDF material for positive electrode slurry, characterized in that: The PVDF material has the following structural formula: ;in, G1 is a co-grafted functional part, including one or more of vinyl trimethoxysilane, styrene ethyl trimethoxysilane, 3-(methacryloyloxy) propyl trimethoxysilane, vinyl tri(2-methoxyethoxy) silane, and (4-vinylphenylmethyl) trimethylsilane; G2 is the dispersion function part, and its structure is as follows: , The R1 and R2 groups are long-chain alkane structures with 1 to 8 carbon atoms, olefins containing unsaturated bonds, or cyclic structures, wherein at least one chain is carboxyl-terminated; the number of repeating units x is 10-40; G3 is the anti-gel functional part, and its structure is as follows: , The R3 group is a hydrogen atom, a methyl group or an acetyl group having 1 to 2 carbon atoms; the R4 and R5 groups are an alkyl group having 1 to 7 carbon atoms, an alkyl group having 1 to 4 carbon atoms and end-capped with a hydroxyl group, or an aromatic group having 6 to 8 carbon atoms.

2. The anti-gel dispersion PVDF material for positive electrode slurry according to claim 1, characterized in that: In the dispersing functional part G2, the monomer composed of R1 and R2 groups includes one or more of maleic anhydride, maleic acid, α-linolenic acid, oleic acid, linoleic acid, and arachidonic acid; the monomer composed of the repeating unit number x is allyl polyethylene glycol with a molecular weight of 500-1800.

3. The anti-gel dispersion PVDF material for positive electrode slurry according to claim 1, characterized in that: In the anti-gel functional part G3, the substance composed of R3 and R4 groups includes one or more of phenylhydrazine, acetylphenylhydrazine, 2-hydrazineethanol, ethylhydrazine, and benzylhydrazine; the substance composed of R5 groups includes one or more of acetylhydrazine, dibutylhydrazine, 4-hydroxybenzoylhydrazine, 4-hydroxyphenylacetylhydrazine, caproylhydrazine, caprylhydrazine, phenylhydrazine, phenylacetylhydrazine, and phenoxyacetylhydrazine.

4. The method for preparing the dispersed anti-gel functional PVDF material for positive electrode slurry according to any one of claims 1 to 3, characterized in that: The steps include: S1, drying PVDF powder in an oven; S2, mixing PVDF powder with initiator, dispersing functional part, co-grafting functional part and anti-gel functional part; S3, start the twin-screw extruder to preheat, and set the parameters; S4, injecting the uniformly mixed sample from the injection port of the twin-screw extruder, extruding through the twin-screw shear mixing reaction, and gradually transferring the material from the first section of the extruder to the sixth section for discharge; S5. Pass the extruded product through a cooling water tank, and use a pelletizer to pelletize the product after water cooling and drying.

5. The method for preparing the dispersed anti-gel functional PVDF material for positive electrode slurry according to claim 4, characterized in that: In step S1, the molecular weight of the PVDF powder is 200000-500000; the temperature of the oven is 80-120°C, and the drying time is 12-24h.

6. The method for preparing the dispersed anti-gel functional PVDF material for positive electrode slurry according to claim 4, characterized in that: In step S2, the mass fractions of each reaction component are: 100 parts of PVDF; 0.1-0.3 parts of initiator; 5-10 parts of dispersion functional part; 1-5 parts of co-grafting functional part; 2-5 parts of anti-gel functional part; the initiator is one or more combinations of benzoyl peroxide, diisopropylbenzene peroxide, dodecanoyl peroxide, di-tert-butylcumyl peroxide, and tert-butyl perbenzoate, preferably dodecanoyl peroxide.

7. The method for preparing the dispersed anti-gel functional PVDF material for positive electrode slurry according to claim 4, characterized in that: In step S4, the twin-screw extruder is provided with six temperature control zones, which are: section I 80±2°C, section II 100±2°C, section III 150±2°C, section IV 170±2°C, section V 170±2°C, and section VI 175±2°C.

8. Dispersed anti-gel functional PVDF material for positive electrode slurry prepared by the method according to any one of claims 4 to 7.

9. Use of the dispersed anti-gel functional PVDF material according to claim 8 as positive electrode slurry for lithium batteries.

Citation Information

Patent Citations

  • Positive electrode slurry and preparation method thereof, and lithium ion battery and preparation method thereof

    CN113659145A

  • Lithium-supplementing binder, lithium-supplementing positive electrode slurry, preparation method of lithium-supplementing positive electrode slurry and lithium ion battery

    CN117059810A

  • PVDF (Polyvinylidene Fluoride) material with high compatibility and adhesion and preparation method thereof

    CN117946338A

  • Preparation method of positive electrode binding material with self-repairing and dispersing functions, positive electrode slurry and preparation method thereof, and preparation method of positive electrode plate

    CN118360015A